Microbial community structure reveals instability of nutritional symbiosis during the evolutionary radiation of Amblyomma ticks. Issue 5 (23rd February 2020) - Binetruy, Florian; Buysse, Marie; Lejarre, Quentin; Barosi, Roxanne; Villa, Manon; Rahola, Nil; Paupy, Christophe; Ayala, Diego; Duron, Olivier
Abstract: Mutualistic interactions with microbes have facilitated the adaptation of major eukaryotic lineages to restricted diet niches. Hence, ticks with their strictly blood‐feeding lifestyle are associated with intracellular bacterial symbionts through an essential B vitamin supplementation. In this study, examination of bacterial diversity in 25 tick species of the genus Amblyomma showed that three intracellular bacteria, Coxiella ‐like endosymbionts (LE), Francisella ‐LE and Rickettsia, are remarkably common. No other bacterium is as uniformly present in Amblyomma ticks. Almost all Amblyomma species were found to harbour a nutritive obligate symbiont, Coxiella ‐LE or Francisella ‐LE, that is able to synthesize B vitamins. However, despite the co‐evolved and obligate nature of these mutualistic interactions, the structure of microbiomes does not mirror the Amblyomma phylogeny, with a clear exclusion pattern between Coxiella ‐LE and Francisella ‐LE across tick species. Coxiella ‐LE, but not Francisella ‐LE, form evolutionarily stable associations with ticks, commonly leading to co‐cladogenesis. We further found evidence for symbiont replacements during the radiation of Amblyomma, with recent, and probably ongoing, invasions by Francisella ‐LE and subsequent replacements of ancestral Coxiella ‐LE through transient co‐infections. Nutritional symbiosis in Amblyomma ticks is thus not a stable evolutionary state, but instead arises from conflicting origins between unrelated but competing symbionts with similar metabolic capabilities.